Public guarantees, private banks' incentives, and corporate outcomes: Evidence from the COVID-19 crisis - Gabriel Jiménez; Luc Laeven; David Martinez-Miera; José-Luis Peydró (European Central Bank (ECB), 2024)
We show that public guaranteed loans (PGL) increase credit availability improving real effects, but private banks' incentives imply that weaker banks shift riskier corporate loans to taxpayers. We exploit credit register data during the COVID-19 shock in Spain, and a stylized model guides the empirics. Unlike non-PGL, banks provide more PGL to riskier firms in which banks have higher pre-crisis shares of firm total credit. Importantly, these effects are stronger for weaker banks. Results using firm(-bank) fixed effects and loan volume versus price information suggest a credit supply-driven mechanism. Moreover, exploiting exogenous variation across similar firms with differing PGL access, we confirm these findings, and we additionally show that PGL increases banks' overall lending and credit share, with positive effects for firm survival and investment.
Keywords: G01; G21; G38; E62; H81; 330; Banking; Private incentives; COVID-19; Public guarantees; Risk-shifting